Impact des incitations à l’investissement du gouvernement fédéral canadien dans le secteur manufacturier, de 1965 à 1974 - Le Goff, Jean-Pierre (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractThe Canadian federal government calls upon substantial fiscal incentives between 1965 to 1974 to increase the flow of capital expenditures in the manufacturing sector, in order to reduce regional disparities, to alleviate an excessive unemployment rate and to insure a higher growth rate. The objective of our research is to evaluate the effectiveness of these incentives in inducing larger investment expenditures. We use econometric investment functions based on neoclassical and "hybrid" models of firm behavior, applied to Canadian yearly manufacturing time series from 1946 to 1974.The neoclassical and hybrid models agree that the incentives have a substantial impact during the years 65-69; and a marginal impact during the 69-74 years.The neoclassical model explains the marginal impact of incentives in the 69-74 period by a displacement through time of investment projects; there is an acceleration-deceleration effect attributed to the incentives. Investment expenditures of the 69-74 period are submitted to an upward pressure because of the 69-74 incentives, and to a downward pressure because of a deceleration effect associated with the 65-69 incentives.We conclude that the incentives are effective in the short run in stimulating investment expenditures (the mean lag of their impact is approximately eighteen months) but that an acceleration-deceleration effect shows up after three years.